Water and Environmental Considerations for the Design and Development of Citrus Groves in Florida - Brian Boman; Nigel Morris; Mark Wade (EDIS, 2002)
This is Circular 1419, one of a series of the Department of Agricultural and Biological Engineering, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2002.